Validating happiness scale for the elderly: A confirmatory factor analysis study in Indonesia - Adriani, Yufi (Institut Agama Islam Negeri Langsa, 2025)
This study addressed the need for a validated instrument to measure happiness among elderly individuals in Indonesia. The research aimed to examine the construct validity of a modified version of The Happiness Scale Interval Study (HSIS). Data were collected from 211 elderly individuals aged 60 years and above residing in Jakarta using a non-probability convenience sampling method. Confirmatory Factor Analysis (CFA) with LISREL 8.70 software was employed to test the unidimensionality and construct validity of the scale. The initial model showed unsatisfactory fit, but after allowing for correlated errors among certain items, the model achieved a good fit with a final Chi-square value of 25.43, p-value = .22884, and RMSEA = .032. The results indicate that all items significantly measure a single factor of happiness, confirming the construct validity of the modified HSIS for elderly populations in Jakarta. This study provides evidence for the validity of this happiness scale as a tool for future research on happiness and well-being among the elderly population in Indonesia, informing the development of targeted interventions.